Pengaruh Budaya Organisasi Terhadap Komunitas Internal dan Kolaborasi Tim - Munawir, A.; Hasibuan, Wildan Anshori; Destika, Aulia Rahman; Kesuma, Galih Ardi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This article aims to explore the impact of organizational culture on internal communication and team collaboration through a qualitative approach with a literature review. The research examines various sources, including journals, books, and articles, that discuss the concepts of organizational culture, internal communication, and team collaboration. The analysis reveals that an organizational culture that supports transparency, openness, and appreciation for diversity contributes to improved internal communication and harmonious team collaboration. These findings highlight that a positive organizational culture can create a work environment that fosters team synergy and enhances overall organizational performance.